Pemberdayaan Potensi Desa Kedongdong Kidul melalui Gerakan Literasi Digital - Bambang Firmansyah; Ferika Maulana; Siti Konaah (IAI Bunga Bangsa Cirebon, 2021)
Kedongdong Kidul Village has a lot of potential from the tourism sector, cottage industry, and education sector. However, information on Kedongdong Kidul village is still considered scarce when looking for data sources via the internet. Through Community Service Lectures with the Asset Based Community Development (ABCD) method which emphasizes two main objectives, namely: first, to publicize village potential through social media; second, digital literacy skills for the community are expected to be a solution to this gap. This service is carried out for 40 days through collecting village potential data, making village potential profiles and providing assistance in the form of social media management workshops and digital literacy skills for the community. This service results in digital literacy and a high increase in community participation in developing village potential through the use of information technology. The very good response from the village government and the community resulted in a new trend, namely